Immunologic changes during unplanned treatment interruptions of highly active antiretroviral therapy in children with human immunodeficiency virus type 1 infection. - Gibb, D; Duong, T; Leclezio, V; Walker, A; Verweel, G; Dunn, D (2004)
BACKGROUND: There are few data on the decline of CD4 cells or percentage during unplanned treatment interruptions in HIV-infected children. METHODS: Data were analyzed on children undergoing interruptions of three or four drug antiretroviral therapy (HAART) in the United Kingdom and Irish Collaborative HIV Paediatric Study and from Sophia Children's Hospital, Rotterdam. Children were included if they had taken HAART continuously for 3 months or longer before interruption and stopped for at least 4 weeks. The effects of CD4 at treatment initiation and of age, CD4, HIV RNA and disease stage at interruption on the CD4 decline during interruption were explored with linear mixed models. RESULTS: Seventy-one children (median age, 7.0 years) had experienced 82 unplanned interruptions of median duration 4.1 (interquartile range, 2.3 to 7.6) months. HAART was restarted after 59 (72%) interruptions (17 with the same and 42 with a new regimen). In children restarting HAART, median CD4% increased toward preinterruption levels by 6 months, when 46% had HIV RNA <400 copies/ml (vs. 15% at interruption). The rate of CD4% decline in 51 children with a median of 3 (range, 2 to 10) CD4 measurements was 0.52% per month (6.2% annually); it was independent of age, CD4 at HAART, preinterruption CD4 or HIV RNA or previous AIDS. CONCLUSIONS: Although the average CD4 decline after stopping HAART appears similar to that in adults, large variability suggests that when designing pediatric trials of planned treatment interruptions, interruption length could be determined by time taken for CD4 to decline below a threshold, rather than by imposing interruptions of fixed duration.